The impact of digital transformation on the country's social progress - Jana Hornungová; Petrová Kateřina (Trends Economics and Management, 2022)
Purpose of the article: The purpose of this paper is to investigate whether there is a relationship between the level of digitalisation and social stability (satisfaction) in EU countries through two main indices. There are many predominantly benefits associated with digitalisation, which can be at the macro, micro, and personal level of the individual. For example, economic growth, increasing productivity, well-being for people or better transparency. Methodology/methods: The DESI and WHI index data, as well as the GDP per capita, were analysed using statistical methods, specifically Pearson's correlation coefficient and regression analysis. Scientific aim: The aim is to identify the relationship between the DESI and WHI and then determine the relationship between these indices and the GDP per capita. Findings: According to the basic statistic results, the highest value of the DESI and WHI indicator was obtained in Finland. Luxembourg had the highest reported GDP per capita. The lowest results were achieved in Romania (DESI) and Bulgaria (WHI and GDPC). A strong positive relationship was found across all relationships analysed (DESI-WHI, DESI-GDPC and WHI-GDPC). In the case of DESI and WHI, the model captures 64.9% of the data; in the case of DESI and GDPC, 46.7%, and in the case of WHI and GDPC, the model reflects 58.9% of the data. For all combinations, a regression function was determined to be linear and increasing. Thus, it means that for all combinations, if one variable increases, the other variable will also increase at the same time. The economic growth, as measured by the GDP per capita, can be well explained by (is influenced by) the DESI index and is also positively influenced by the WHI. Conclusions: The survey shows that digitalisation needs to be given enough attention because this factor is closely linked to social progress and not only that; the pandemic has clearly shown us that digital services are our future in many areas.
Keywords: I31; M15; M21; 650; digital transformation; social progress; Digital Economy and Society Index (DESI); World Happiness Index (WHI); correlation analysis; regression analysis